The Plot of Victory in Shajarat al-Bambar (Bumber Tree) - Sami Abdulnabi, Prof. Dr. Israq (Basra studies journal, 2026)
The study examines the concept of the plot of victory in book of ( Shajarat al-Bambar) by Faten Al-Sarraf, considering it as an autobiographical/narrative text that reconfigures the female self through memory, not according to a logic of defeat nor of lamentation, but through a narrative strategy that transforms personal experience into an act of symbolic victory. The study proceeds from the assumption that the text does not present victory as a complete external event, but rather as a gradual narrative process shaped through the reinterpretation of pain, deprivation, and marginalization.